Whale‐watching trips in Peru lead to increases in tourist knowledge, pro‐conservation intentions and tourist concern for the impacts of whale‐watching on humpback whales - García‐Cegarra, Ana M.; Pacheco, Aldo S. (Aquatic conservation, 2017)
Since the implementation of the commercial whaling ban in the 1980s, whale‐watching has become the most important economic activity involving whales worldwide. Whale‐watching is promoted as a platform for education and conservation awareness of marine biodiversity. In Peru, where cetacean species are still in jeopardy, whale‐watching may play an important part in promoting the protection of these species. This study aimed to determine the degree of whale‐watching tourists' knowledge regarding cetacean ecology and conservation status and to evaluate if whale‐watching tours could serve as platforms for educating the public and raising conservation awareness. The results of 196 closed‐ended questionnaires and 20 open‐ended interviews conducted before and after whale‐watching tours, during the humpback whale season (winter–spring 2014) in northern Peru, revealed an overall lack of knowledge concerning the presence of species of cetaceans in Peruvian waters and threats to marine biodiversity. However, after the whale‐watching excursion, participants said they would be more willing to change their behaviour with respect to cetacean conservation and marine environment protection. This study suggests that whale‐watching platforms, when implemented with adequate interpreters, can serve as a source of environmental education and can raise conservation awareness. This is an important conservation strategy to consider in countries, such as Peru, where by‐catch and direct hunting are decimating local cetacean populations.